2017
DOI: 10.1186/s12889-017-4557-4
|View full text |Cite|
|
Sign up to set email alerts
|

Illegal gold miners in French Guiana: a neglected population with poor health

Abstract: BackgroundIn French Guiana, a French overseas territory in South America, 6 to 10 thousands undocumented persons work illegally in gold mining sites in the Amazonian forest. Precarious life conditions lead to poor health but few data exist on the health status of illegal gold miners in French Guiana. The objective of this article was to describe the sociodemographic and health status of this vulnerable population.MethodA prospective cross-sectional survey was conducted in 2015 on gold mine supply sites at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
129
0
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(144 citation statements)
references
References 40 publications
2
129
0
13
Order By: Relevance
“…Legal exploitation is more industrial. The proportion of these two mining statuses varies greatly from one country to the other (Table 1) [7][8][9][10][11][12][13][14][15][16][17].…”
Section: Gold Mines In the Amazon: Context And Health Impact Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Legal exploitation is more industrial. The proportion of these two mining statuses varies greatly from one country to the other (Table 1) [7][8][9][10][11][12][13][14][15][16][17].…”
Section: Gold Mines In the Amazon: Context And Health Impact Diseasesmentioning
confidence: 99%
“…In this context, the disease burden is heavy for people working in the gold mining sector. The active gold miner population is estimated at 800,000 persons in the Amazon (Table 1), to which must be added people who gravitate around them such as logisticians, cooks, commercial traders, or gold miners' families [6,11,15]. Health facilities are rare or even absent not only from illegal sites, but also in legal mines [].…”
Section: Gold Mines In the Amazon: Context And Health Impact Diseasesmentioning
confidence: 99%
“…Statistical analysis concerning mercury exposure and hematological effect was reported in 17 studies as follows: 11 were mean difference (Student's t-test; Wilcoxon) 12,22,23,24,42,43,44,45,46,47,48 ; eight (two data not shown) were correlation coefficient r (Pearson; Spearman) 12,22,23,24,43,44,49,50 ; three were regression coefficient β (linear models) 51,52,53 ; two (one data not shown) were prevalence 49,54 and one was odds ratio (data not shown) 48 . The results reported for mean difference were: four studies evaluated anemia and two did not find difference (p = 0.05 and p = 0.183) 42,48 and other two found it (p = 0.016 and p < 0.05) 43,47 ; one study found difference for leukopenia and neutropenia (p < 0.05) 46 ; five studies analyzed lymphocytes and three did not find difference (p not informed) 22,23,24 and one did find (p < 0.05) 12 ; one study evaluated polycythemia and did find difference (p < 0.05) 45 .…”
Section: Resultsmentioning
confidence: 99%
“…One found positive association for neutrophilia and basophilia (β = 1.38, 95%CI: 0.11; 2.65 and β = 0.04, 95%CI: -0.03; 0.11) 51 . For prevalence, one study reported 22% (95%CI: 18.0; 25.9) for anemia 54 .…”
Section: Resultsmentioning
confidence: 99%
“…Economic activities such as overexploitation of fishing grounds (Hutchings 2000), intensive nickel or gold mining (e.g. Greenland, New Caledonia or French Guiana (Douine et al 2017)) jeopardise the health of key ecosystems and people and are generating conflict. Natural and anthropogenic climatic changes put additional pressures on ecosystems and biodiversity (Thomas et al 2004) as they are expected to increase risks of diseases, challenge vegetation sensitive to temperature increases, accelerate coral bleaching (Heron et al 2016) and increase extreme weather events.…”
Section: Introductionmentioning
confidence: 99%